Development of the pulmonary fibrosis, pulmonary vascular resistance, six minute walk distance, B-type natriuretic peptide, age (PVD-B65) risk score for patients with chronic lung disease and pulmonary hypertension - Shameek Gayen; Jay Pescatore; Matthew Bittner; Mario Naranjo; Gerard J. Criner; Sheila Weaver; Temple Lung Center Pulmonary Vascular Disease Working Group (BMC Pulmonary Medicine)
Abstract Background Pulmonary hypertension (PH) confers increased mortality in patients with chronic lung disease, yet there remains a lack of validated risk assessment tools to prognosticate these patients. We aimed to create a risk assessment tool to stratify patients with chronic lung disease and PH by risk of one-year mortality from time of PH diagnosis. Methods This was a retrospective cohort study of patients with chronic lung disease and PH. We identified predictors of one-year mortality via multivariable Cox regression and assigned point values to the identified predictors based on their hazard ratios to comprise the risk score. Patients were stratified into low, intermediate, and high-risk based on total scores. Kaplan–Meier survival analysis comparing the stratified groups was performed. Internal statistical validation was performed via Cox regression with bootstrapping. Results The identified predictors of one-year mortality that comprised our risk assessment tool were pulmonary fibrosis without emphysema, pulmonary vascular resistance > 5 WU, six-minute walk distance < 150 m, BNP > 200 pg/mL, and age > 65 years (PVD-B65). Once patients were stratified into the three risk groups, Kaplan–Meier survival analysis demonstrated significant differences in one-year survival between the subgroups (logrank p = 0.002). The risk assessment model demonstrated internal validation via bootstrapping (p < 0.05). Conclusion The PVD-B65 risk assessment tool is a novel, internally validated one-year mortality risk calculator for patients with chronic lung disease and PH that encompasses factors related to pulmonary parenchymal and vascular remodeling. It may help risk stratify and guide therapeutic interventions in patients with chronic lung disease and PH.